Incomplete Augmented Lagrangian Preconditioner for Steady Incompressible Navier-Stokes Equations - Ning-Bo Tan; Ting-Zhu Huang; Ze-Jun Hu (The Scientific World Journal)
An incomplete augmented Lagrangian preconditioner, for the steady incompressible Navier-Stokes equations discretized by stable finite elements, is proposed. The eigenvalues of the preconditioned matrix are analyzed. Numerical experiments show that the incomplete augmented Lagrangian-based preconditioner proposed is very robust and performs quite well by the Picard linearization or the Newton linearization over a wide range of values of the viscosity on both uniform and stretched grids.